Consumer Behavior Model and Economic Space Characteristics in Explaining the Dynamics of MSMEs in the Sampit Urban Area - Muamar; Andri Riyadi; Bio Ertanto (International Journal of Science and Environment (IJSE), 2026)
This study aims to analyze the influence of economic space characteristics on the dynamics of MSMEs through consumer behavior in the Sampit urban area. The background of the study is based on the development of MSMEs which is not always followed by equal business success, even though business actors are in relatively similar economic spaces. The study uses a quantitative approach with an explanatory design. Primary data were obtained through questionnaires to 65 MSME actors in the trade and service sectors selected using purposive sampling. Data analysis was carried out using Structural Equation Modeling based on Partial Least Square (SEM-PLS) using SmartPLS 4. The results showed that economic space characteristics have a positive and significant effect on consumer behavior (path coefficient = 0.723; p-value = 0.000), economic space characteristics have a positive and significant effect on MSME dynamics (path coefficient = 0.479; p-value = 0.001), and consumer behavior has a positive and significant effect on MSME dynamics (path coefficient = 0.304; p-value = 0.034). However, consumer behavior was not shown to significantly mediate the relationship between economic space characteristics and MSME dynamics (indirect effect = 0.219; p-value = 0.064). This finding confirms that MSME dynamics in the Sampit urban area are more dominantly influenced directly by the structure of economic space rather than through consumer behavior mechanisms. This study contributes to the development of an integrative model of economic space and consumer behavior in explaining urban MSME dynamics.